Issues Faced By Lady Health Visitors (Lhvs) Working For Polio Immunization Campaigns In District Quetta, Pakistan - Zarak, Muhammad Samsoor; Abdullah, Ahmed; Arshad, Zara; Haq, Noman Ul; Nasim, Aqeel; kakar, Saliha; sana, Hamaiyal; khan, Jaffar; Khan, Alamzeb; Ullah, Asad (Journal of Medical Biomedical and Applied Sciences, 2018)
Objective: To assess the problems faced by Lady Health Visitors during polio vaccination campaignin district Quetta.Method: This study is a qualitative study based on interviews with LHVs in Quetta. The saturation point was 8interviews however, a total of 10 interviews were conducted for accuracy. The subjects were selected based on snowballtechnique. Data was transcribed, and frequencies were drawn on SPSS version 20, after three themes were generatedusing the standard procedure namely; Pre- campaign issues, Issues during campaigning and Post- campaign issues.Result: The most prevalent pre-campaign issue recorded was conveyance issue i.e. travel of LHVs from their houseto Polio center and vice versa. The most common issue faced during the door to door campaign was rude behavior ofpeople and taunting. Character calling was the second most common issue recorded. Furthermore, not opening doorsfor LHVs was the thirst commonest issue. victimization and harassment by pedestrians and public. The most commonpost-campaign issues recorded was delay in provision of pay to the LHVs along with non-cooperation of departmentsin solving issues of LHVs.Conclusion: This study is an admonition for concerned departments and authorities. With such issues being faced,appropriate incentives should be given to the on duty LHVs. Departments need to solve the issues on priority basis.Most incidences of victimization by public are based on their religious views hence it is strongly recommended thatreligious authorities be involved in the campaigns to play their effective role in changing the perceptions of people aboutPolio immunization campaigns. Nonetheless, mass media campaigns are recommended to aware the community aboutPolio and the role of LHVs in eradication of polio from Pakistan.